Major Superficial White Matter Abnormalities in Huntington's Disease - Phillips, Owen R.; Joshi, Shantanu H.; Squitieri, Ferdinando; Sanchez-Castaneda, Cristina; Narr, Katherine; Shattuck, David W.; Caltagirone, Carlo; Sabatini, Umberto; Di Paola, Margherita (Frontiers in Neuroscience, 2016)
Background The late myelinating superficial white matter at the juncture of the cortical gray and white matter comprising the intracortical myelin and short-range association fibers has not received attention in Huntington’s disease. It is an area of the brain that is late myelinating and is sensitive to both normal aging and neurodegenerative disease effects. Therefore, it may be sensitive to Huntington’s disease processes. Methods Structural MRI data from 25 Pre-symptomatic subjects, 24 Huntington’s disease patients and 49 healthy controls was run through a cortical pattern-matching program. The surface corresponding to the white matter directly below the cortical gray matter was then extracted. Individual subject’s Diffusion Tensor Imaging (DTI) data was aligned to their structural MRI data. Diffusivity values along the white matter surface were then sampled at each vertex point. DTI measures with high spatial resolution across the superficial white matter surface were then analyzed with the General Linear Model to test for the effects of disease. Results There was an overall increase in the axial and radial diffusivity across much of the superficial white matter (p < 0.001) in Pre-symptomatic subjects compared to controls. In Huntington’s disease patients increased diffusivity covered essentially the whole brain (p < 0.001). Changes are correlated with genotype (CAG repeat number) and disease burden (p < 0.001). Conclusions This study showed broad abnormalities in superficial white matter even before symptoms are present in Huntington’s disease. Since the superficial white matter has a unique microstructure and function these abnormalities suggest it plays an important role in the disease.